Genome-wide association studies of seedling quantitative trait loci against salt tolerance in wheat - Khan, Rao Waqar Ahmad; Khan, Rao Sohail Ahmad; Awan, Faisal Saeed; Akrem, Ahmed; Iftikhar, Arslan; Anwar, Farhana Naureen; Alzahrani, Hind A. S.; Alsamadany, Hameed; Iqbal, Rana Khalid (Frontiers in Genetics, 2022)
Salinity is one of the significant factors in decreasing wheat yield and quality. To counter this, it is necessary to develop salt-tolerant wheat varieties through conventional and advanced molecular techniques. The current study investigated identify quantitative trait loci (QTLs) in response to salt stress among worldwide landraces and improved varieties of wheat at the seedling stage. 125 landraces and wheat varieties were subjected under salt treat (50mM, 100mM, and 150mM) with control. Morphological seedling traits i.e. shoot length (SL), root length (RL), fresh and dry shoot root weight (FSW, FRW, FRW, DRW) for salinity tolerance were observed to assess salt-tolerance and genetic analysis using SNP data through DArT-seq. The results showed that, at the seedling stage, 150 mM NaCl treatment decreased shoot length (SL), root length (RL), fresh and dry weights of shoot and root (FSW, FRW, FRW, DRW). The root length (RL) and dry root weight (DRW) were the most affected traits at the seedling stage. Effective 4417 SNPs encompassing all the chromosomes of the wheat genome with marker density i.e. 37% fall in genome B, genome D (32%), and genome A (31%). Five loci were found on four chromosomes 6B, 6D, 7A, and 7D showing strong associations with the root length (RL), fresh shoot weight (FSW), fresh root weight (FRW), and dry root weight (DRW) at p < 0.03 significance level. The positive correlation was found among all morphological traits under study.